Outreach to Promote Management of Cardiovascular Risk in Primary Care Among Patients With Rheumatoid Arthritis Seen in Rheumatology Practice. Issue 3 (27th January 2020) - Persell, Stephen D.; Lee, Ji Young; Lipiszko, Dawid; Peprah, Yaw A.; Ruderman, Eric M.; Schachter, Michael; Majka, Darcy S.
Abstract : Objective: Rheumatoid arthritis (RA) confers a 1.5‐ to 2.0‐fold increased risk of cardiovascular disease (CVD). A prior multifaceted quality improvement approach to improving CVD preventive care increased CVD risk factor assessments, but there was no significant effect on the management of risk factors. We tested the impact of adding a proactive outreach strategy promoting primary care treatment of CVD risk factors among patients with RA through their rheumatology practice. Methods: Through electronic health record searches, we identified patients with RA who were potential candidates for hypertension treatment initiation or intensification, statin therapy, or a smoking‐cessation intervention. A nonclinician care manager contacted patients by phone and mail on behalf of the rheumatologists, provided information about the identified risk factor(s), recommend follow‐up with primary care physicians (PCPs), sent correspondence to PCPs, and followed up with patients to see what actions had been taken. We measured preventive cardiology quality indicators and compared preintervention and intervention time periods using interrupted time series methods. Results: During the 6‐month intervention period, the proportion of patients prescribed at least moderate‐intensity statin treatment for primary prevention rose from 18.4% to 23.8%. The rate of increase was 1.06% greater per month than during the preceding period ( P < 0.001). Rates of increase in hypertension diagnosis and control improved more rapidly during this phase ( P < 0.001 for each) and reversed preceding negative trends. Conclusion: Implementing proactive nonclinician outreach to encourage primary care–based treatment of CVD risk factors was associated with increases in statin prescribing and in hypertension diagnosis and control. Smoking was not affected.